Territorialização da Atenção Primária à Saúde: avaliação e perspectivas no município de Santo Antônio de Jesus, Bahia - Andrade, Ismael Mendes (2015)
The territorialization stands out as a technique which “creates”political territories for Health, is also an organizing tool in healthcare practices, included in the National Policy of Primary Care through attached territory, and allows for the planning, decentralized programming and the development of intersectoral actions in line with the principle of equality established by the Unified Health System. Therefore the main objective of the study was to analyze the territorialization in Primary Health Care in Santo Antônio de Jesus, Bahia. The methodology became the choice for exploratory approach from the quantitative nature. Therefore held survey of bibliographic references on the Unified Health System (SUS), on territory, health and primary health care and verification of documents related to legislation also ordinances and resolutions on the subject, made her survey of cartographic base the census tracts of the city under study, and research of the administrative organization of the Municipal Health Department, georeferencing of the Family Health Units and application forms with the Community Health Agents of the service areas of the Health Unit. The result showed need for territorial parameterized as many health facilities exceeded the population limits; weaknesses to the employment contract of top-level professionals. And contribution of adequacy proposals, in addition to thematic maps for organization in health districts and consequently in health units.